Surface-treated calcium carbonate filler, and resin composition and molded article using the same
Patent Information
- Application Number
- JP2023131669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-10
AI Technical Summary
【0016】 本発明によれば、耐熱性に優れ、樹脂と容易に混合することのできる樹脂組成物を提供することができる。本発明の表面処理炭酸カルシウム填料はまた、樹脂中の分散性が良好であり、溶融混練の際の樹脂焼けや凝集物の発生や、ストレーナーの目詰まりなどの発生を低減することができ、操業安定性に優れた樹脂組成物を提供することができる。さらに、例えば、本発明の表面処理炭酸カルシウム填料とポリオレフィン系樹脂とを用いて得られたフィルムは、耐候性や耐熱性の面で強度劣化が起こり難いという特徴を有する。
Smart Images

Figure 2025026212000001 
Figure 2025026212000002 
Figure 2025026212000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-treated calcium carbonate filler, and a resin composition and a molded article each using the same. [Background technology]
[0002] Polyolefin resins are characterized by excellent rigidity, impact resistance, heat resistance, moldability, transparency, chemical resistance, etc., and are widely used in various applications, such as various industrial materials, automobile-related parts, various containers for medical and cosmetic use, and various films and fibers for daily necessities and industrial use, for example, by combining them with calcium carbonate inorganic pigments. They are also known as relatively environmentally friendly resins, and are expected to be used as base materials in green infrastructure applications. On the other hand, it is also desired to further improve the weather resistance, heat resistance, and strength of resin compositions containing such polyolefin resins that are melt-kneaded to produce products.
[0003] In addition, efforts have been made to stabilize resin compositions by adding metal soaps such as calcium stearate, phenolic antioxidants, and phosphorus-based antioxidants to the resins to be melt-kneaded. Alternatively, efforts have been made to add calcium carbonate treated with a fatty acid such as stearic acid or stearic acid soap to these resins, thereby combining the function of calcium carbonate with the role of enhancing the stability of the resin (see, for example, Patent Document 1). The resin compositions obtained in this way are useful as materials for porous films that can be used, for example, as battery separators (Patent Documents 2 to 4).
[0004] On the other hand, in order to obtain such a resin composition, there have been proposed a method in which a resin and an antioxidant such as a phenolic or phosphorus-based antioxidant are mixed in advance using a mixer such as a super mixer or a tumbler mixer, and then melt-kneaded; a method in which the resin and additives are separately and simultaneously charged and melt-kneaded; and a method in which a side feed is performed from the middle of the kneader into the molten resin.
[0005] However, although the reason is unclear as to whether the antioxidant does not reach every corner of the obtained resin composition or does not fully function due to thermal degradation of the antioxidant, all of these methods result in the antioxidant not reaching every corner of the obtained resin composition, the antioxidant does not fully function due to thermal degradation, and the thermal stability of the molded resin composition may be insufficient. For this reason, there is a demand for the development of an additive that can reach every corner of the resin composition, not be thermally deteriorated, fully function as a sliding agent, and further improve the stability of the resin composition. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-363443 A [Patent Document 2] JP 2006-169421 A [Patent Document 3] International Publication No. 2007 / 088707 [Patent Document 4] JP 2004-196917 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to solve the above-mentioned problems, and an object of the present invention is to provide a surface-treated calcium carbonate filler which can improve all of weather resistance, heat resistance and strength of a resin composition obtained by kneading the filler with a resin such as a polyolefin-based resin, and a resin composition and a molded article each using the same. [Means for solving the problem]
[0008] The present invention provides a surface-treated calcium carbonate filler that satisfies the following formulas (a), (b), and (c): (a) 2.0≦Sw≦20.0(m 2 / g) (b) 300≦Pw≦5000(ppm) (c)0.01≦Tw≦0.30 (mass%) (Sw is the BET specific surface area (m 2 / g), The Pw is the content (ppm) of the phosphorus element in the surface-treated calcium carbonate filler measured by an inductively coupled plasma (ICP) optical emission spectrometer, The Tw is a weight loss value (mass%) of the surface-treated calcium carbonate filler at 140° C. to 220° C. measured by a differential thermobalance apparatus.
[0009] In one embodiment, the surface treated calcium carbonate filler of the present invention further satisfies the following formula (d): (d) 0.80≦bw≦1.50 The bw is a hue change rate calculated by the following formula using a yellow value (b value) measured by a spectrophotometer before and after continuous heating at 140° C. for 48 hours for a paste in which the surface-treated calcium carbonate filler and dioctyl phthalate (DOP) are mixed in a mass ratio of 3:7: Hue change rate (bw) = (b value of paste after heating / b value of paste before heating) It is.
[0010] In one embodiment, the surface treated calcium carbonate filler of the present invention further satisfies the following formulas (e), (f) and (g): (e) 0.10≦D50≦2.00(μm) (f) 0.9≦(D90-D10) / D50≦2.0 (g) Da≦5.0(μm) The D50 is a 50% diameter (μm) accumulated from the small particle side in a volume particle size distribution of the surface-treated calcium carbonate filler measured with a laser diffraction particle size distribution measuring device, The D90 is a 90% diameter (μm) accumulated from the small particle side in the volume particle size distribution of the surface-treated calcium carbonate filler measured with the laser diffraction particle size distribution measurement device, The D10 is a 10% diameter (μm) accumulated from the small particle side in the volume particle size distribution of the surface-treated calcium carbonate filler measured with the laser diffraction particle size distribution measurement device, The Da is the maximum particle size (μm) in the volume particle size distribution of the surface-treated calcium carbonate filler measured with the laser diffraction particle size distribution measurement device.
[0011] In one embodiment, the surface-treated calcium carbonate filler of the present invention is used to constitute a polyolefin-based resin composition.
[0012] The present invention also relates to a resin composition comprising a resin and the above-mentioned surface-treated calcium carbonate filler.
[0013] In one embodiment, the resin is a polyolefin resin.
[0014] The present invention also relates to a molded article made from the above resin composition.
[0015] In one embodiment, the molded article of the present invention has the form of a film. Effect of the Invention
[0016] According to the present invention, a resin composition having excellent heat resistance and capable of being easily mixed with a resin can be provided. The surface-treated calcium carbonate filler of the present invention also has good dispersibility in a resin, and can reduce occurrence of resin burning or agglomerates during melt kneading, clogging of a strainer, and the like, and can provide a resin composition having excellent operational stability. Furthermore, for example, a film obtained by using the surface-treated calcium carbonate filler of the present invention and a polyolefin resin has a feature that strength deterioration is unlikely to occur in terms of weather resistance and heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] 1. Surface-treated calcium carbonate filler First, the surface-treated calcium carbonate filler of the present invention will be described.
[0018] The surface-treated calcium carbonate filler of the present invention satisfies the following formulas (a), (b), and (c).
[0019] (a) BET specific surface area (Sw) The surface-treated calcium carbonate filler of the present invention has a predetermined BET specific surface area (Sw;m 2 In the present invention, Sw of the surface-treated calcium carbonate filler is 2.0≦Sw≦20.0(m 2 / g), and preferably 3.0≦Sw≦15.0(m 2 / g), and more preferably 5.0≦Sw≦12.0(m 2 / g). The Sw of the surface-treated calcium carbonate filler is 2.0 (m 2 When the Sw of the surface-treated calcium carbonate filler is less than 20.0(m / g), the primary particles become too large, which causes a decrease in strength of the resin composition when the filler is blended in the resin composition. In addition, when the primary particles are large, for example, undesired protrusions are formed on the surface of the obtained resin molded body, and the sliding property of the resin molded body may be decreased. 2 When the surface-treated calcium carbonate filler exceeds 100% by mass % (1 / g), the crystallinity of calcium carbonate constituting the surface-treated calcium carbonate filler becomes weak, and a resin composition obtained by mixing the surface-treated calcium carbonate filler with a polyolefin-based resin or the like cannot have sufficient weather resistance or heat resistance. In addition, as the primary particles become smaller, the cohesive force between the particles becomes larger, so that, for example, the primary particles cannot be sufficiently dispersed when kneaded with a resin, and undesired protrusions are formed on the surface of a resin molded body, which may result in a decrease in the slidability of the resin molded body.
[0020] (Method of measuring Sw) The Sw of the surface-treated calcium carbonate filler can be measured, for example, using Macsorb HM model-1201 manufactured by Mountech Co., Ltd. as follows.
[0021] Specifically, about 300 mg of the surface-treated calcium carbonate filler to be subjected to the measurement is set in a measuring device, and a heat treatment is performed at 200°C for 10 minutes in a mixed gas atmosphere of nitrogen and helium as a pretreatment, and then low-temperature and low-humidity physical adsorption is performed in an environment of liquid nitrogen, whereby Sw is measured.
[0022] Sw can be controlled by varying various conditions in producing the surface-treated calcium carbonate filler of the present invention. Examples of conditions that can control Sw within the above range include the concentration of milk of lime used in the carbonation reaction, the temperature employed in the carbonation reaction, the concentration of carbon dioxide gas used, and the type of additive used in the carbonation reaction, as well as a combination of these, as described below. When such conditions are not set sufficiently, it may be difficult to obtain a surface-treated calcium carbonate filler that satisfies the above range of Sw.
[0023] (b) Phosphorus content (Pw) measured using an inductively coupled plasma (ICP) optical emission spectrometer The surface-treated calcium carbonate filler of the present invention has a predetermined phosphorus content (Pw; ppm) measured by an ICP optical emission spectrometer. In the present invention, the Pw of the surface-treated calcium carbonate filler is 300≦Pw≦5000 (ppm), preferably 400≦Pw≦3000 (ppm), and more preferably 500≦Pw≦1500 (ppm). When the Pw is less than 300 (ppm), the filler itself does not have sufficient heat resistance. When the Pw exceeds 5000 (ppm), the obtained surface-treated calcium carbonate filler is likely to aggregate, so that the dispersibility in a resin is reduced, and further, a satisfactory thermal stability cannot be obtained in a resin composition.
[0024] (Method of measuring Pw) Pw can be measured, for example, using an ICP optical emission spectrometer SPS3500 manufactured by SII NanoTechnology Inc. as follows.
[0025] (1) First, about 1,000 mg of the surface-treated calcium carbonate filler to be measured is placed in a crucible and fired in an electric furnace at 300°C for 3 hours. (2) After firing, a small amount (e.g., about 60 mL) of distilled water and 7.5 mL of 1.38 N nitric acid (nitric acid (1.38) for measuring hazardous metals, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) are added to a 200 mL beaker, and the mixture is boiled on an electric stove and slowly cooled. (3) 100 μL of yttrium standard solution (Y1000 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) is placed in a 100 mL measuring flask, the above-mentioned cooled mixture is added, and the solution is made up to 100 mL with distilled water. (4) Next, the solution is filtered through 5C filter paper, and a sample for ICP measurement is prepared from the resulting filtrate. (5) After that, the content (ppm) of elemental phosphorus contained in this sample is measured by the ICP optical emission spectrometer.
[0026] (c) Weight loss value (Tw) The surface-treated calcium carbonate filler of the present invention has a predetermined weight loss value (Tw; mass%) at 140°C to 220°C measured by a differential thermobalance apparatus. In the present invention, Tw of the surface-treated calcium carbonate filler is 0.01≦Tw≦0.30 (mass%), preferably 0.01≦Tw≦0.20 (mass%), and more preferably 0.01≦Tw≦0.15 (mass%). When Tw is less than 0.01 (mass%), there is no significant problem in the physical properties of the filler itself, but a large production load is required to increase the crystallinity of calcium carbonate constituting the filler. When Tw exceeds 0.30 (mass%), the obtained surface-treated calcium carbonate filler does not have sufficient heat resistance, and it is difficult to obtain a resin composition excellent in all of weather resistance, heat resistance, and strength.
[0027] (Method of measuring Tw) Tw can be measured using a differential thermobalance (for example, DTG-60A manufactured by Shimadzu Corporation) as follows.
[0028] (1) First, about 30 mg of the surface-treated calcium carbonate filler is weighed into a platinum sample pan and set in the measuring instrument. (2) Then, the temperature of the measuring device is raised from room temperature to 550°C at a heating rate of 30°C / min, and measurement is performed, and the weight loss value (mass%) per 1 g of the surface-treated calcium carbonate filler from 140°C to 220°C is calculated.
[0029] Further, it is more preferable that the surface-treated calcium carbonate filler of the present invention satisfies the following formula (d) in addition to the above formulas (a) to (c):
[0030] (d) Hue change rate (bw) In the surface-treated calcium carbonate filler of the present invention, a paste (also referred to as "DOP paste") obtained by mixing the surface-treated calcium carbonate filler and dioctyl phthalate (DOP) in a mass ratio of 3 to 7 has a predetermined hue change rate (bw) calculated from a yellow value (b value) measured by a spectrophotometer before and after continuous heating at 140°C for 48 hours with reference to JIS K 7368:1999 (Plastics-Polypropylene and propylene copolymers-Method for measuring thermo-oxidative stability in air-Oven method). Note that this hue change rate (bw) is calculated from the following formula: Hue change rate (bw) = (b value of paste after heating / b value of paste before heating)
[0031] In the present invention, the bw of the surface-treated calcium carbonate filler is preferably 0.80≦bw≦1.50, and more preferably 1.00≦bw≦1.20. When the bw is less than 0.80, there is no significant problem in the physical properties of the filler itself, but a large production load is required to increase the crystallinity of calcium carbonate constituting the filler. When the bw is more than 1.50, the obtained surface-treated calcium carbonate filler does not have sufficient heat resistance, and it is difficult to obtain a resin composition excellent in all of weather resistance, heat resistance, and strength.
[0032] (How to measure bw) bw can be measured, for example, as follows.
[0033] (1) First, a surface-treated calcium carbonate filler and dioctyl phthalate (DOP) are weighed in a mass ratio of 3:7, and mixed in a degassing mixer (e.g., Mazerustar manufactured by Kurabo Industries, Ltd.) to prepare a DOP paste. (2) Next, the color difference of this DOP paste is measured with a spectrophotometer (for example, ZE-2000 manufactured by Nippon Denshoku Industries Co., Ltd.) as the "b value of the paste before heating." (3) The DOP paste is then placed in a glass petri dish and heated continuously for 48 hours in a forced air oven set at 140°C (i.e., a heat resistance test is performed). (4) After removing from the oven and allowing to cool, the color difference of the DOP paste is measured as the "b value of the paste after heating" using a spectrophotometer (for example, ZE-2000 manufactured by Nippon Denshoku Industries Co., Ltd.). (5) From the “b value of the paste before heating” and the “b value of the paste after heating” obtained above, the hue change rate bw before and after heating is calculated (bw = (b value of the paste after heating / b value of the paste before heating)).
[0034] Furthermore, the surface-treated calcium carbonate filler of the present invention preferably satisfies one or more of the following formulas (e), (f) and (g), in addition to the above formulas (a) to (c), and more preferably satisfies all of the formulas (e), (f) and (g).
[0035] (e) 50% diameter (D50) accumulated from the small particle side in the volumetric particle size distribution The surface-treated calcium carbonate filler of the present invention preferably has a 50% diameter (D50; μm) accumulated from the small particle side in a volume particle size distribution measured by a laser diffraction particle size distribution measuring device that satisfies a predetermined range. In the present invention, the D50 of the surface-treated calcium carbonate filler is preferably 0.10≦D50≦2.00 (μm), more preferably 0.30≦D50≦0.80 (μm). Surface-treated calcium carbonate particles having a D50 of less than 0.10 (μm) can be technically obtained, but since more advanced and precise technology is required, there is a risk of an increase in production cost. When the D50 exceeds 2.00 (μm), the cohesive force of secondary particles constituted by aggregates of primary particles becomes large, and the secondary particles cannot be sufficiently dispersed when kneaded with a resin, and clogging of a strainer may easily occur.
[0036] (How to measure D50) D50 can be measured, for example, using a laser diffraction particle size distribution analyzer (MT-3300EX II manufactured by Microtrack Bell Corporation) as follows, together with D10, D90 and Da described below. (1) First, about 0.3 g of a sample of the surface-treated calcium carbonate filler and 50 mL of a medium are combined and suspended in a 100 mL beaker. (2) Next, the contents in the beaker are dispersed by irradiating them with ultrasonic waves at 300 μA for 1 minute using a tip-type ultrasonic disperser (for example, US-300T manufactured by Nippon Seiki Seisakusho Co., Ltd.). (3) Then, the volumetric particle size distribution of the surface-treated calcium carbonate particles in the sample is measured using a laser diffraction particle size distribution measuring device (MT-3300EX II manufactured by Microtrack-Bell Corporation).
[0037] Media that can be used in the above measurement include methanol, ethanol, and combinations thereof.
[0038] D50 can be controlled by varying various conditions when producing the surface-treated calcium carbonate particles constituting the filler of the present invention. Conventionally, various methods for dispersing calcium carbonate particles have been known, such as a method of finely crushing the particles to reduce D50 using mechanical techniques such as a ball mill, a sand grinder mill, an impact mill, a homogenizer, and a dyno mill. In the carbon dioxide gas synthesis method of wet synthesis, it is preferable to use Ostwald ripening, which grows the calcium carbonate particles to a certain particle size and disperses them, as a method for controlling the particle size of the calcium carbonate particles.
[0039] (f) Sharpness index of volumetric particle size distribution ((D90-D10) / D50) The surface-treated calcium carbonate filler of the present invention preferably has a sharpness index ((D90-D10) / D50) in a volume particle size distribution measured with a laser diffraction particle size distribution measuring device that satisfies a predetermined range. Here, D50 is as described above, D90 is a 90% diameter (μm) accumulated from the small particle side in the volume particle size distribution measured with the laser diffraction particle size distribution measuring device, D10 is a 10% diameter (μm) accumulated from the small particle side in the volume particle size distribution measured with the laser diffraction particle size distribution measuring device, and Da is a maximum particle diameter (μm) in the volume particle size distribution measured with the laser diffraction particle size distribution measuring device.
[0040] In the present invention, the sharpness index ((D90-D10) / D50) of the surface-treated calcium carbonate filler is preferably 0.9≦(D90-D10) / D50≦2.0, and more preferably 1.0≦(D90-D10) / D50≦1.5. It is technically possible to obtain a surface-treated calcium carbonate filler having a sharpness index of less than 0.9, but since a more advanced and precise technique is required, there is a risk of an increase in production costs. When the sharpness index of the surface-treated calcium carbonate filler exceeds 2.0, the variation in size of voids formed in a molded product (e.g., a film) obtained by kneading the obtained surface-treated calcium carbonate filler with a resin increases, and it may become difficult to obtain a porous film having a uniform in-plane distribution of voids.
[0041] (Method for measuring sharpness index ((D90 - D10) / D50)) D10, D90, and Da that constitute the sharpness index can be measured in the same manner as the measurement of D50 using, for example, the laser diffraction particle size distribution measuring device (e.g., MT - 3300EX II manufactured by Microtrac Bell Co., Ltd.) described for the measurement of D50 above.
[0042] The sharpness index can be controlled by varying various conditions during the production of the surface - treated calcium carbonate filler of the present invention. Methods for reducing the sharpness index of calcium carbonate particles (e.g., making the particle size distribution sharp by reducing coarse and fine particles) include mechanical methods such as the aforementioned ball mill, sand grinder mill, impact mill, homogenizer, dyno - mill, etc., and methods that utilize the difference in sedimentation rates in water according to particle size such as elutriation (suihi) to separate fine and coarse particles. However, from the viewpoint that it is easy to reduce the sharpness index by improving the particle size uniformity of calcium carbonate particles, it is preferable to use Ostwald ripening.
[0043] (g) Maximum particle diameter (Da) in volume particle size distribution The surface - treated calcium carbonate filler of the present invention preferably satisfies that the maximum particle diameter (Da) is within a predetermined range in the volume particle size distribution measured by a laser diffraction particle size distribution measuring device. In the present invention, Da of the surface - treated calcium carbonate filler is preferably Da ≤ 5.0 (μm) (i.e., 0 < Da ≤ 5.0 (μm)), and more preferably Da ≤ 3.0 (μm) (i.e., 0 < Da ≤ 3.0 (μm)). When Da exceeds 5.0 μm, for example, when forming and stretching a resin composition of the obtained surface - treated calcium carbonate filler and resin, it may break and the surface - treated calcium carbonate filler may easily fall off, unwanted protrusions may be formed on the surface of the obtained resin molded body, and problems such as a decrease in the slidability of the resin molded body may occur.
[0044] (Method for measuring Da) Da can be measured in the same manner as for measuring D50 above, for example, using a laser diffraction particle size distribution measuring device (e.g., MT-3300EX II manufactured by Microtrack Bell Corporation) described for measuring D50 above.
[0045] Da can be controlled by varying various conditions in producing the surface-treated calcium carbonate filler of the present invention. As a method for reducing the maximum particle size (Da) in the volume particle size distribution, it is preferable to carry out classification using gravity, centrifugal force, flotation, etc., such as decantation, and removal with a sieve, filter, etc., for the purpose of removing impurities and coarse particles at the stage of an aqueous slurry form, or to carry out a classification operation such as air classification at the stage of a powder form to remove aggregates generated by drying.
[0046] (Surface-treated calcium carbonate filler that has been surface-treated with a surface treatment agent) As described above, the surface-treated calcium carbonate filler of the present invention satisfies all of the formulas (a), (b), and (c), and at least one of the formulas (d), (e), (f), and (g) as necessary. Such a surface-treated calcium carbonate filler contains surface-treated calcium carbonate particles that have been surface-treated with a surface treatment agent, and is preferably constituted of the surface-treated calcium carbonate particles as a main component.
[0047] Here, the term "surface-treated" as used in the present specification is used to mean the "state" of the surface of the surface-treated calcium carbonate filler and / or the surface-treated calcium carbonate particles. On the other hand, the term "surface-treated / has been surface-treated" as used in the present specification is used to mean that calcium carbonate particles that have not been subjected to surface treatment (i.e., untreated) have been subjected to a process for modifying (surface treating) the surface thereof.
[0048] The surface-treated calcium carbonate particles in the present invention are unmodified (before surface treatment) calcium carbonate particles which have been surface-treated with a surface treatment agent.
[0049] (Unmodified calcium carbonate particles) Here, the unmodified calcium carbonate particles are, from the viewpoint of degassing properties when kneaded with a resin, rather than natural white saccharified limestone (heavy calcium carbonate) which contains a large amount of fine particles, Synthetic calcium carbonate particles (e.g., light / colloidal calcium carbonate) prepared by a synthetic method in which natural gray dense limestone is burned. Synthetic calcium carbonate particles can be controlled uniformly, and hydrochloric acid-insoluble ores that are the source of relatively coarse particles have been removed in advance. Synthetic calcium carbonate crystal forms include three types of crystals: vaterite crystals, which are the most unstable in aqueous systems and thermodynamically, metastable aragonite crystals, and stable calcite crystals. Those containing calcite crystals as the main component are preferred because of their good stability.
[0050] Such unmodified calcium carbonate particles can be produced by a known carbon dioxide gas method, for example, by adding water to quicklime obtained by calcining gray dense limestone to form calcium hydroxide, which is then reacted with carbon dioxide gas generated during calcination. The calcium carbonate slurry reacted by this carbon dioxide gas method can be adjusted by Ostwald aging until it has a desired BET specific surface area, thereby obtaining desired calcium carbonate particles.
[0051] For the purpose of further enhancing the weather resistance and heat resistance of a resin composition when blended with a polyolefin-based resin, which is the main object of the present invention, a seed chemical reaction method in which calcium carbonate particles undergoing Ostwald ripening are used as seed particles and a carbonation reaction is carried out thereon is preferably used in combination with the method of preparing desired calcium carbonate particles by Ostwald ripening, since this method can provide calcium carbonate particles with higher crystallinity.
[0052] Furthermore, for the purpose of further increasing the uniformity of the synthetic calcium carbonate particles, the calcium carbonate particles may be obtained by separating a light liquid (fine particle side) and a heavy liquid in an appropriate ratio using a separation device such as a liquid cyclone machine from a water slurry used to obtain the synthetic calcium carbonate particles or a water slurry containing calcium hydroxide prior to the production of the synthetic calcium carbonate particles.
[0053] (Surface treatment agent) The surface treatment agent is used for the unmodified calcium carbonate particles for the purpose of improving the flowability of the powder, the alkali resistance and activity resistance of calcium carbonate, and other properties of the calcium carbonate filler. Examples of the surface treatment agent include phosphorus-based compounds. Examples of the phosphorus-based compounds include inorganic phosphoric acids, organic phosphoric acids, and combinations thereof.
[0054] Examples of inorganic phosphoric acids include orthophosphoric acid, phosphorous acid, phosphinic acid, pyrophosphoric acid, polyphosphoric acid (e.g., tripolyphosphoric acid), and condensed phosphoric acid, their salts (e.g., alkali metal salts such as sodium salts and potassium salts; alkaline earth metal salts such as magnesium salts; aluminum salts), and combinations thereof.Specific examples of salts of inorganic phosphoric acids include sodium phosphate, potassium phosphate, aluminum phosphate, sodium polyphosphate, sodium pyrophosphate, sodium tripolyphosphate, sodium acid tripolyphosphate, sodium tetrapolyphosphate, sodium pentapolyphosphate, sodium metaphosphate, sodium hexametaphosphate, sodium metaphosphate, and sodium ultraphosphate, and combinations thereof.
[0055] Examples of organic phosphoric acids include hydroxyethylidene diphosphonic acid, nitrilotrismethylenephosphonic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, ethylenediamidetetramethylenephosphonic acid, and phenylphosphonic acid; and salts thereof; esters such as trimethyl phosphoric acid ester, triethyl phosphoric acid ester, tripropyl phosphoric acid ester, mono- or dimethyl phosphoric acid ester, dimethyl phenylphosphonic acid ester, diethyl phenylphosphonic acid ester, trimethyl phosphite (methyl phosphorous acid ester), triethyl phosphite (ethyl phosphorous acid ester), acidic phosphoric acid esters; and combinations thereof.
[0056] As the above-mentioned surface treatment agent, inorganic phosphoric acids such as sodium hexametaphosphate, sodium polyphosphate, sodium pyrophosphate, sodium tripolyphosphate, and sodium ultraphosphate, and organic phosphoric acids such as nitrilotrismethylenephosphonic acid and trimethyl phosphoric acid ester, and combinations thereof can be preferably used as the phosphorus-based compound, because they can satisfactorily improve all of the weather resistance, heat resistance, and strength of the resulting resin composition.
[0057] In the present invention, the surface treatment agent may contain other surface treatment agents in addition to the above phosphorus-based compound.
[0058] Examples of the other surface treatment agent include fatty acid / fatty acid soap-based surface treatment agents, coupling agent-based surface treatment agents, and surfactant-based surface treatment agents, and combinations thereof. The other surface treatment agents may be commercially available products.
[0059] Examples of fatty acid / fatty acid soap-based surface treatment agents include fatty acids and fatty acid salts, as well as combinations thereof.
[0060] Examples of fatty acids include saturated fatty acids, unsaturated fatty acids, alicyclic carboxylic acids, and resin acids, and combinations thereof.
[0061] Examples of saturated fatty acids include capric acid, caproic acid, lauric acid, myristic acid, palmitic acid, stearic acid, and isostearic acid, and combinations thereof. Examples of unsaturated fatty acids include oleic acid, linoleic acid, and linolenic acid, and combinations thereof. Examples of alicyclic carboxylic acids include naphthenic acid, which has a carboxyl group at the end of a cyclopentane ring or a cyclohexane ring. Examples of resin acids include abietic acid, pimaric acid, and neoabietic acid, and combinations thereof.
[0062] The fatty acid salts include alkali metal salts (e.g., sodium salts, potassium salts), alkaline earth metal salts (e.g., calcium salts, magnesium salts), ammonium salts, and amine salts of the above fatty acids, as well as combinations thereof. It is preferable to use alkali metal salts of fatty acids because they have high solubility in water and are easy to treat the calcium carbonate surface.
[0063] Examples of the fatty acid salts include saturated fatty acid salts such as potassium laurate, potassium myristate, potassium palmitate, sodium palmitate, potassium stearate, sodium stearate, and sodium isostearate; unsaturated fatty acid salts such as potassium oleate and sodium oleate; and alicyclic carboxylates such as sodium naphthenate and lead cyclohexylbutyrate, potassium abietic acid, and sodium abietic acid, as well as combinations thereof.
[0064] The fatty acid / fatty acid soap-based surface treatment agent may be, for example, modified or unmodified fatty acids derived from animals or plants, such as mixed fatty acids commonly used in the art, such as beef tallow fatty acid, palm oil fatty acid, palm kernel oil fatty acid, soybean oil fatty acid, alkali metal salts thereof, or so-called hydrogenated mixed fatty acids or alkali metal salts thereof, which are obtained by hydrogenating these mixed fatty acids to reduce the degree of unsaturation.
[0065] In addition, when a fatty acid is used as it is as the fatty acid, it is preferable to dissolve the fatty acid in advance in hot water heated to a temperature equal to or higher than the melting point of the fatty acid to be used, add a known emulsifier such as an anionic surfactant or a nonionic surfactant to the water, and emulsify the fatty acid using an emulsifying disperser such as a homomixer or a homogenizer, and then add the fatty acid to the unmodified calcium carbonate, for the reason that the surface treatment of the unmodified calcium carbonate particles can be more uniform.
[0066] Among the above fatty acids, unsaturated fatty acids are not only highly soluble in water but also have a low melting point, so that they can be more uniformly surface-treated on the surface of unmodified calcium carbonate particles, while from the viewpoint of heat resistance, unsaturated fatty acids are characterized in that they are easily thermally deteriorated due to the presence of unsaturated double bonds. For this reason, in the present invention, the fatty acids are preferably saturated fatty acids and / or saturated fatty acid salts, because the concerns about thermal deterioration, such as those of the above unsaturated fatty acids, are eliminated in advance. Alternatively, the total amount of saturated fatty acids and saturated fatty acid salts is preferably 90% by mass or more, more preferably 100% by mass, based on the total mass of the fatty acids.
[0067] Examples of coupling agent-based surface treatment include vinyl silane coupling agent, amino silane coupling agent, phenyl silane coupling agent, epoxy silane coupling agent, styryl silane coupling agent, acrylic silane coupling agent, methacryl silane coupling agent, isocyanurate silane coupling agent, ureido silane coupling agent, mercapto silane coupling agent, and isocyanate silane coupling agent, and combinations thereof.Vinyl silane coupling agent is preferred because it can impart good strength to the obtained resin composition, and phenyl silane coupling agent is preferred because it can impart good weather resistance and heat resistance to the obtained resin composition.
[0068] Examples of surfactant-based surface treatment agents include aromatic sulfonic acids and / or resin acids and their salts or esters; alcohol-based surfactants; polyhydric alcohols; sorbitan fatty acid esters; amide-based surfactants; amine-based surfactants; polyoxyalkylene alkyl ethers; polyoxyethylene nonylphenyl ether; sodium alpha-olefin sulfonate; long-chain alkyl amino acids; amine oxides; alkylamines; and quaternary ammonium salts; and combinations thereof.
[0069] In consideration of good compatibility and dispersibility with a resin when the surface-treated calcium carbonate filler to be obtained is blended with the resin, the other surface treatment agent is preferably a fatty acid / fatty acid soap-based surface treatment agent, more preferably a saturated fatty acid and an unsaturated fatty acid, or a salt thereof, and most preferably a saturated fatty acid salt.
[0070] (Surface treatment of unmodified calcium carbonate particles) The surface treatment of unmodified calcium carbonate particles with the above-mentioned surface treatment agent is carried out, for example, as follows.
[0071] For the surface treatment of unmodified calcium carbonate particles, either a general dry treatment or a general wet treatment may be adopted. Preferably, a method of adding the above-mentioned surface treatment agent to a water slurry containing unmodified calcium carbonate particles may be adopted. Such a method is generally called a wet treatment, and is preferred in that it can appropriately balance the degree of surface treatment of calcium carbonate particles and production efficiency.
[0072] The amount of the surface treatment agent, particularly the amount of the phosphorus-based compound, used varies depending on the BET specific surface area and / or amount of the unmodified calcium carbonate particles, the content of the phosphorus element contained in the phosphoric acid itself, the type of the resin to be finally kneaded, the kneading conditions, etc., and is not particularly limited, and can be appropriately selected by a person skilled in the art so as to satisfy the above-mentioned Pw range.
[0073] The order of treatment of unmodified calcium carbonate particles with the above-mentioned surface treatment agents, particularly the phosphorus-based compound and the other surface treatment agent, is not particularly limited. For example, unmodified calcium carbonate particles may be first treated with the other surface treatment agent and then treated with the phosphorus-based compound. Alternatively, unmodified calcium carbonate particles may be first treated with the phosphorus-based compound and then treated with the other surface treatment agent. Alternatively, unmodified calcium carbonate particles may be treated with the phosphorus-based compound and the other surface treatment agent together, i.e., simultaneously.
[0074] The temperature employed for the surface treatment is not particularly limited, and an appropriate temperature may be selected by one skilled in the art.
[0075] After the above surface treatment, the resulting particles may be powdered through any operation such as dehydration, drying, and pulverization, for example, according to a conventional method.
[0076] The dehydration can be performed by using a filter press or a centrifugal dehydrator to the slurry containing the surface-treated calcium carbonate particles. For drying, a hot air type dryer such as a micron dryer that can dry the surface-treated calcium carbonate particles efficiently by directly contacting the surface-treated calcium carbonate particles with high-temperature hot air may be used, or a heat transfer type dryer such as a CD dryer that brings the surface-treated calcium carbonate particles into contact with a heating plate and dries the particles indirectly through the heating plate may be used.
[0077] In this manner, surface-treated calcium carbonate particles that have been surface-treated with a surface treatment agent can be obtained. The surface-treated calcium carbonate particles can be used as they are as a surface-treated calcium carbonate filler that satisfies all of the above formulae (a), (b), and (c), and, if necessary, at least one of the formulae (d), (e), (f), and (g).
[0078] 2.Resin composition Next, the resin composition of the present invention will be described.
[0079] The resin composition of the present invention contains a resin and the above-described surface-treated calcium carbonate filler.
[0080] The resin contained in the resin composition is not particularly limited, and examples thereof include polyolefin resins, polystyrene resins, acrylic resins, methacrylic resins, vinyl chloride resins, vinylidene chloride resins, polyamide resins, polyether resins, vinyl acetate resins, and polyvinyl alcohol resins, as well as combinations thereof. Specific examples of polyolefin resins include polyethylene resins such as low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (L-LDPE), and ultra-high molecular weight polyethylene (UHMWPE), polypropylene resins, ethylene-propylene copolymers, and copolymers of ethylene or propylene with other monomers. The resin may be derived from petroleum, plants (e.g., bioplastics), or a combination thereof. In the present invention, the resin is preferably a polyolefin resin, since the molding temperature is relatively low compared to engineering plastics and the like, and the resin has sufficient heat resistance at a temperature at which the surface-treated calcium carbonate particles can exhibit heat resistance.
[0081] The content of the surface-treated calcium carbonate filler contained in the resin composition is not necessarily limited since it varies depending on the type of resin used in combination, the application of the obtained resin composition, and desired physical properties, for example, but is, for example, 0.05 parts by mass to 100 parts by mass, preferably 50 parts by mass to 100 parts by mass, and more preferably 70 parts by mass to 100 parts by mass relative to 100 parts by mass of the resin. When the content of the surface-treated calcium carbonate filler contained in the resin composition exceeds 100 parts by mass (i.e., exceeds the content of the resin), the kneadability with the resin may decrease and the hue (whiteness) may easily decrease due to deterioration of the resin. When the content of the surface-treated calcium carbonate filler contained in the resin composition is less than 0.05 parts by mass, the obtained resin composition may not have sufficient heat resistance.
[0082] In addition, the resin composition of the present invention may contain, as other additives, lubricants such as fatty acids, fatty acid amides, ethylene bisstearic acid amide, and sorbitan fatty acid esters; plasticizers; stabilizers such as heat stabilizers and light stabilizers; antioxidants; ultraviolet absorbers; neutralizing agents; antifogging agents; antiblocking agents; antistatic agents; slip agents; and colorants; as well as combinations thereof. The content of the other additives is not particularly limited, and an appropriate amount can be selected by one skilled in the art within a range that does not inhibit the effects of the above-mentioned surface-treated calcium carbonate filler.
[0083] The resin and the surface-treated calcium carbonate filler, as well as other additives contained as necessary, can be mixed using a known mixer such as a super mixer, a Henschel mixer, a tumbler mixer, a ribbon blender, etc. After being mixed in the mixer, the resin composition is heated and kneaded using a single-screw or twin-screw extruder, a kneader mixer, a Banbury mixer, etc., and once processed into a pellet shape as a master batch, which can be melted and formed into a film using a known molding machine such as a T-die extrusion or an inflation molding machine.
[0084] 3. Molded products The molded article of the present invention is composed of the above-mentioned resin composition.
[0085] The molded article of the present invention preferably has the form of a film.
[0086] For example, the resin composition kneaded as described above can be formed into a sheet shape using a T-die or the like, and then uniaxially or biaxially stretched to obtain a porous film having fine pores on the surface. Alternatively, after the kneading, a film can be formed using a known molding machine such as T-die extrusion or inflation molding, and the film can be treated with an acid to dissolve the surface-treated calcium carbonate filler present inside, thereby obtaining a porous film having fine pores on the surface. Furthermore, if necessary, a plurality of T-die extruders in the above process may be stacked, or the film may be laminated after stretching to form a multilayer film. In addition, for the purpose of imparting printability to the film, a surface treatment such as plasma discharge may be applied to the film surface to coat an ink-receiving layer. EXAMPLES
[0087] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, % means % by mass, and parts means parts by mass, unless otherwise specified.
[0088] The materials, surface-treated calcium carbonate fillers, and pellets described in each of the Examples and Comparative Examples were evaluated as follows.
[0089] (1) BET specific surface area of unmodified calcium carbonate Approximately 300 mg of the unmodified calcium carbonate particles used in each Example and Comparative Example was placed in a measuring device (Macsorb HM model-1201 manufactured by Mountec Co., Ltd.), and subjected to a pretreatment of heating at 200°C for 10 minutes in a mixed gas atmosphere of nitrogen and helium, followed by low-temperature, low-humidity physical adsorption in a liquid nitrogen environment to measure the BET specific surface area (m 2 / g) was measured.
[0090] (2) BET specific surface area (Sw) of surface-treated calcium carbonate filler About 300 mg of the surface-treated calcium carbonate filler obtained in each of the Examples and Comparative Examples was placed in a measuring device (Macsorb HM model-1201 manufactured by Mountec Co., Ltd.), and a heat treatment was performed at 200°C for 10 minutes in a mixed gas atmosphere of nitrogen and helium as a pretreatment, and then low-temperature and low-humidity physical adsorption was performed in a liquid nitrogen environment to measure the BET specific surface area (m 2 / g) was measured.
[0091] (3) Phosphorus content (Pw) of the surface-treated calcium carbonate filler measured by an inductively coupled plasma (ICP) emission spectrometer
[0092] About 1000 mg of the surface-treated calcium carbonate filler obtained in each of the Examples and Comparative Examples was charged into a crucible and fired in an electric furnace at 300°C for 3 hours. After firing, a small amount of distilled water and 7.5 mL of 1.38N nitric acid (nitric acid (1.38) for measuring harmful metals, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added to a 200mL beaker containing the mixture, and the mixture was boiled on an electric stove and gradually cooled. The mixture after the gradual cooling was added to a 100mL measuring flask containing 100μL of yttrium standard solution (Y1000, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and the mixture was further diluted with distilled water to 100mL. Next, the mixture was filtered with 5C filter paper, and a sample for ICP measurement was prepared from the obtained filtrate. Thereafter, the phosphorus element content (ppm) of this sample was measured using an inductively coupled plasma (ICP) optical emission spectrometer (SPS3500 ICP optical emission spectrometer manufactured by SII NanoTechnology Inc.).
[0093] (4) Weight loss value (Tw) of surface-treated calcium carbonate filler at 140℃ to 220℃ About 30 mg of the surface-treated calcium carbonate filler obtained in each of the Examples and Comparative Examples was weighed out in a platinum sample pan and set in a differential thermobalance device (DTG-60A manufactured by Shimadzu Corporation). Thereafter, the temperature of the measuring device was increased from room temperature to 550°C at a temperature increase rate of 30°C / min, and measurement was performed, and a weight loss value (mass%) from 140°C to 220°C per 1g of the surface-treated calcium carbonate filler was calculated.
[0094] (5) Color change rate of surface-treated calcium carbonate filler (bw) The surface-treated calcium carbonate filler obtained in each of the Examples and Comparative Examples and dioctyl phthalate (DOP) were weighed in a mass ratio of 3:7, and mixed in a degassing mixer (Mazerustar manufactured by Kurabo Industries, Ltd.) to prepare a DOP paste. Next, the color difference of this DOP paste was measured as the "b value of the paste before heating" by a spectrophotometer (ZE-2000 manufactured by Nippon Denshoku Industries Co., Ltd.). Thereafter, the DOP paste was placed in a glass petri dish and heated continuously for 48 hours in a forced-air oven set at 140°C. After removing from the oven and allowing to cool, the color difference of the DOP paste was measured as the "b value of the paste after heating" by the above spectrophotometer.
[0095] From the obtained "b value of the paste before heating" and "b value of the paste after heating", the hue change rate bw before and after heating was calculated according to the following formula: bw = (b value of paste after heating / b value of paste before heating).
[0096] (6) D50, sharpness index ((D90-D10) / D50) and Da of surface-treated calcium carbonate filler About 0.3 g of the surface-treated calcium carbonate filler obtained in each of the Examples and Comparative Examples and 50 mL of methanol were added to a 100 mL beaker. Next, the contents in the beaker were irradiated with ultrasonic waves at 300 μA for 60 seconds using, for example, an ultrasonic disperser US-300T manufactured by Nippon Seiki Seisakusho Co., Ltd., to disperse the contents to obtain a sample. Thereafter, the volumetric particle size distribution of the surface-treated calcium carbonate particles in the sample was measured using a laser diffraction particle size distribution measuring device (MT-3300EX II manufactured by Microtrack Bell Co., Ltd.). From the results of the obtained volumetric particle size distribution, the values of D50, D10, D90 and Da, as well as the sharpness index ((D90-D10) / D50) calculated using the same were obtained.
[0097] (7) Thermo-oxidative stability of pellets From the pellets obtained in each Example and Comparative Example, a test piece of 50 × 50 × 1 mm was prepared using a tabletop hot press G-12 manufactured by Orihara Manufacturing Co., Ltd., adjusted to 200 ° C. This test piece was heated in air at a set temperature of 140 ° C. using a forced draft oven based on the Japanese Industrial Standard JIS K7368 (Plastics - Polypropylene and propylene copolymers - Measurement method for thermal oxidation stability in air - Oven method) to accelerate deterioration, and the number of days required from the start of the test until local cracks, crumbling and / or discoloration could be visually observed was recorded and evaluated according to the following criteria. ◎: No noticeable changes were observed even after 10 days. ○: Discoloration was observed after 10 days. △: Discoloration and cracks were observed after 10 days. ×: Discoloration and cracking were already observed after 5 days.
[0098] (8) Heat resistance evaluation of pellets The pellets obtained in each Example and Comparative Example were heated in air for 10 days using a forced draft oven at 140°C to accelerate degradation. The MFR value (g / 10 min) of the obtained heat-degraded pellets and the initial pellets (not heat-degraded) was measured at a test temperature of 230°C and a nominal load of 21.6 kg using MELT INDEXER F-F01 manufactured by Toyo Seiki Seisakusho Co., Ltd., based on the Japanese Industrial Standard JIS K7210 (Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) Test Method for Plastics-Thermoplastic Plastics). Furthermore, the change rate (%) of MFR was calculated from the obtained results according to the following formula to evaluate the presence or absence of heat resistance.
[0099]
number
[0100] (7) Evaluation of pellet dispersibility The pellets obtained in each Example and Comparative Example were kneaded and extruded into a twin-screw kneader (2D25W manufactured by Toyo Seiki Co., Ltd.) equipped with a three-piece strainer having mesh openings of 100 μm, 60 μm, and 400 μm, at a cylinder setting temperature of 170° C., a screw rotation speed of 150 rpm, and a feed rate of 6 kg / hour. The resin pressure after 60 minutes was measured, and dispersibility was evaluated according to the following criteria. ⊚: The resin pressure after 60 minutes of kneading was less than 4 MPa. ◯: The resin pressure after 60 minutes of kneading was 4 MPa or more and less than 6 MPa. △: The resin pressure after 60 minutes of kneading was 6 MPa or more and less than 8 MPa. ×: The resin pressure after 60 minutes of kneading was 8 MPa or more, or vent-up occurred before that time due to clogging of the strainer.
[0101] (8) Tensile strength evaluation For the pellets obtained in each Example and Comparative Example, a 200 μm thick film was produced using a tabletop hot press G-12 manufactured by Orihara Manufacturing Co., Ltd., adjusted to 200 ° C. The film was punched out into 20 dumbbell-shaped test pieces using a punching blade, and the thickness of each test piece was measured, and 5 test pieces with a thickness within ± 10% of the average thickness of the 20 pieces were selected. The selected test pieces were subjected to tensile strength evaluation at a test force of 500 N and a test speed of 5 mm / minus using an autograph AG-I manufactured by Shimadzu Corporation based on the Japanese Industrial Standard JIS K7127 (Plastics - Test method for tensile properties - Part 3), and the dispersibility was evaluated according to the following criteria. The tensile strength referred to here indicates the stress measured when the test piece breaks. ⊚: The tensile strength was 33 MPa or more. ◯: The tensile strength was 30 MPa or more and less than 33 MPa. △: The tensile strength was 27 MPa or more and less than 30 MPa. ×: The tensile strength was less than 27 MPa.
[0102] (9) Evaluation of sliding properties: Measurement of static and dynamic friction coefficients For the pellets obtained in each Example and Comparative Example, a test piece of 80 x 200 x 1 mm was prepared using a tabletop hot press G-12 manufactured by Orihara Manufacturing Co., Ltd., adjusted to 200 ° C. The static and dynamic friction coefficients of the test piece were measured using a friction coefficient measuring instrument AN-S2 manufactured by Toyo Seiki Seisakusho Co., Ltd., based on the Japanese Industrial Standard JIS K7125 (Plastics - Films and Sheets - Friction Coefficient Test Method) at a load of 200 g and a test speed of 100 mm / min, and the sliding properties were evaluated according to the following criteria. It should be noted that a lower value of both the static and dynamic friction coefficients indicates a higher sliding property. (Evaluation of static friction coefficient) ⊚: The static friction coefficient was less than 0.60. ◯: The static friction coefficient was 0.60 or more and less than 0.70. △: The static friction coefficient was 0.70 or less and less than 0.80. ×: The static friction coefficient was 0.80 or more. (Evaluation of the coefficient of dynamic and static friction) ⊚: The dynamic friction coefficient was less than 0.40. ◯: The dynamic friction coefficient was 0.40 or more and less than 0.50. △: The dynamic friction coefficient was 0.50 or less and less than 0.60. ×: The dynamic friction coefficient was 0.60 or more. (Overall evaluation of sliding properties) ⊚: The sliding property was extremely good. A: The sliding property was good. Δ: The sliding properties were somewhat good. ×: The sliding properties were poor.
[0103] (Example 1: Preparation of surface-treated calcium carbonate filler (E1)) Gray dense limestone was fired in a kiln using natural gas as a heat source, and the quicklime obtained was dissolved in water to obtain calcium hydroxide slurry with a specific gravity of 1.050. This calcium hydroxide slurry was reacted with CO2 gas discharged from the kiln to obtain a synthetic calcium carbonate slurry with a concentration of 8.0 mass%.
[0104] The resulting synthetic calcium carbonate slurry was subjected to Ostwald aging to obtain a BET specific surface area of 10.0 m 2 After the particles were grown to a specific surface area of 8.0 m / g, 10% by mass of calcium hydroxide was added to the calcium carbonate solids using the resulting calcium carbonate as a seed, and a seed compound was formed by reacting the calcium carbonate with the CO gas discharged from the calcination furnace. 2 / g of calcium carbonate slurry was obtained.
[0105] To this, 0.6% by mass of ultrasodium phosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content and an aqueous solution of a phosphorus-based compound prepared in warm water to a concentration of 10% by mass were added to the calcium carbonate slurry, the mixture was stirred at 60°C for 12 hours, dehydrated to a solid content of 65% by mass using a filter press, dried with a hot air dryer (Dry Meister DMR-1 manufactured by Hosokawa Micron Corporation), impact crushed, and the obtained powder was classified with an air classifier to obtain a surface-treated calcium carbonate filler for polyolefin resin (E1) of Example 1. The physical property values of the obtained surface-treated calcium carbonate filler (E1) are shown in Table 1.
[0106] (Example 2: Preparation of surface-treated calcium carbonate filler (E2)) A surface-treated calcium carbonate filler (E2) was obtained in the same manner as in Example 1 except that, instead of the aqueous solution of the phosphorus-based compound prepared in Example 1, an aqueous solution of a phosphorus-based compound prepared in warm water to have a concentration of 10 mass% and 1.0 mass% of aluminum monophosphate (50% aluminum monophosphate solution manufactured by Taihei Chemical Industry Co., Ltd.) relative to the calcium carbonate solid content was added to the calcium carbonate slurry, and a fatty acid salt prepared by saponifying 1.6 mass% of a saturated fatty acid (NAA-122 (lauric acid: 99%) manufactured by NOF Corporation) with caustic soda relative to the calcium carbonate solid content was added to the aqueous solution to have a concentration of 10 mass%. The physical property values of the obtained surface-treated calcium carbonate filler (E2) are shown in Table 1.
[0107] (Example 3: Preparation of surface-treated calcium carbonate filler (E3)) A surface-treated calcium carbonate filler (E3) was obtained in the same manner as in Example 1 except that an aqueous solution of a phosphorus-based compound prepared in such a manner that 0.3 mass% of sodium pyrophosphate (sodium pyrophosphate manufactured by Taihei Chemical Industry Co., Ltd.) relative to the calcium carbonate solid content was added to the calcium carbonate slurry so as to give a concentration of 10 mass% in warm water, instead of the aqueous solution of a phosphorus-based compound prepared in Example 1, and a saturated fatty acid soap (NONSAAL SN-1 (saturated fatty acid rate 100%) manufactured by NOF Corporation) was added to the calcium carbonate slurry so as to give a concentration of 10 mass% in warm water, and a surface-treated calcium carbonate filler (E3) was obtained in the same manner as in Example 1 except that a saturated fatty acid soap (NONSAAL SN-1 (saturated fatty acid rate 100%) manufactured by NOF Corporation) was added to the calcium carbonate slurry so as to give a concentration of 10 mass% in warm water, instead of the aqueous solution of a phosphorus-based compound prepared in Example 1. The physical property values of the obtained surface-treated calcium carbonate filler (E3) are shown in Table 1.
[0108] The NOF Corporation Nonsal SN-1 used above had the following component composition (myristic acid 3 mass%, palmitic acid 27 mass%, stearic acid 66 mass%, and others 4 mass%).
[0109] (Example 4: Preparation of surface-treated calcium carbonate filler (E4)) A surface-treated calcium carbonate filler (E4) was obtained in the same manner as in Example 3, except that an aqueous solution of a phosphorus compound prepared by adding 1.5% by mass of orthophosphoric acid (75% orthophosphoric acid manufactured by Rasa Kogyo Co., Ltd.) to warm water to give a concentration of 10% by mass was used instead of the aqueous solution of a phosphorus compound prepared in Example 3. The physical property values of the obtained surface-treated calcium carbonate (E4) are shown in Table 1.
[0110] (Example 5: Preparation of surface-treated calcium carbonate filler (E5)) A surface-treated calcium carbonate filler (E5) was obtained in the same manner as in Example 3 except that an aqueous solution of a phosphorus compound was prepared in warm water to have a concentration of 10 mass% by adding 0.6 mass% sodium hexametaphosphate (sodium hexametaphosphate manufactured by Taihei Chemical Industry Co., Ltd.) relative to the calcium carbonate solid content, instead of the aqueous solution of a phosphorus compound prepared in Example 3. The physical property values of the obtained surface-treated calcium carbonate filler (E5) are shown in Table 1.
[0111] (Example 6: Preparation of surface-treated calcium carbonate filler (E6)) In the same manner as in Example 1, the obtained synthetic calcium carbonate slurry was subjected to Ostwald aging to obtain a calcium carbonate slurry having a BET specific surface area of 13.0 m 2 A calcium carbonate slurry was obtained in which particles had been grown to a calcium carbonate content of 1000 g / g.
[0112] A surface-treated calcium carbonate filler (E6) was obtained in the same manner as in Example 2 except that this calcium carbonate slurry was used, and instead of the aqueous solution of a phosphorus compound prepared in Example 1, an aqueous solution of a phosphorus compound was prepared by adding 0.3 mass% linitrilotrismethylenephosphonic acid (JPCN-300 manufactured by Johoku Chemical Co., Ltd.) relative to the calcium carbonate solid content to warm water to give a concentration of 10 mass%, and the solution was dried for 2 hours at a steam pressure of 0.25 MPa using a CD dryer manufactured by Kurimoto, Ltd. as a heat transfer dryer. The physical property values of the obtained surface-treated calcium carbonate filler (E6) are shown in Table 1.
[0113] (Example 7: Preparation of surface-treated calcium carbonate filler (E7)) In the same manner as in Example 1, the obtained synthetic calcium carbonate slurry was subjected to Ostwald aging to obtain a calcium carbonate slurry having a BET specific surface area of 10.0 m 2 After the particles were grown to a BET specific surface area of 8.0 m / g, seeding was performed. 2 A calcium carbonate slurry was obtained in which particles had been grown to a calcium carbonate content of 1000 g / g.
[0114] An aqueous solution of a phosphorus-based compound was prepared in warm water by adding 0.6% by mass of ultrasodium phosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to the calcium carbonate slurry to give a concentration of 10% by mass. The solution was stirred at 60°C for 12 hours, dehydrated to a solid content of 65% by mass using a filter press, dried in a hot air dryer (Dry Meister DMR-1 dryer manufactured by Hosokawa Micron Corporation), and crushed by impact to obtain a phosphorus-based compound-treated calcium carbonate powder.
[0115] The obtained phosphorus compound-treated calcium carbonate powder was put into a Super Mixer SMV(G)-100 manufactured by Kawata Co., Ltd., and glycerin (refined glycerin manufactured by Miyoshi Oil Co., Ltd.), which is a polyhydric alcohol, was added as a surface treatment agent at 0.6 mass% relative to the calcium carbonate solid content while stirring, and dry treatment was performed at 110°C for 0.5 hours, followed by impact crushing. The obtained powder was classified by an air classifier to obtain a surface-treated calcium carbonate filler (E7). The physical property values of the obtained surface-treated calcium carbonate filler (E7) are shown in Table 1.
[0116] (Example 8: Preparation of surface-treated calcium carbonate filler (E8)) A surface-treated calcium carbonate filler (E8) was obtained in the same manner as in Example 7 except that a vinyl silane coupling agent (KBM-1003 manufactured by Shin-Etsu Chemical Co., Ltd.) which is a coupling agent was used in an amount of 1.0 mass% relative to the calcium carbonate solid content as a surface treatment agent instead of the surface treatment agent used in Example 7. The physical property values of the obtained surface-treated calcium carbonate filler (E8) are shown in Table 1.
[0117] (Example 9: Preparation of surface-treated calcium carbonate filler (E9)) In the same manner as in Example 1, the obtained synthetic calcium carbonate slurry was subjected to Ostwald aging to obtain a calcium carbonate having a BET specific surface area of 4.0 m 2 After the particles were grown to a specific surface area of 2.8 m / g, 10% by mass of calcium hydroxide was added to the calcium carbonate solids using the resulting calcium carbonate as a seed, and a seed compound was formed by reacting the calcium carbonate with the CO gas discharged from the calcination furnace. 2 / g of calcium carbonate slurry was obtained, and then a phosphorus-based compound-treated calcium carbonate powder was obtained in the same manner as in Example 7.
[0118] A surface-treated calcium carbonate filler (E9) was obtained in the same manner as in Example 7 except that a saturated fatty acid (Sakura stearate beads manufactured by NOF Corporation) was used in an amount of 1.0 mass% relative to the calcium carbonate solid content instead of the surface treatment agent used in Example 7. The physical property values of the obtained surface-treated calcium carbonate filler (E9) are shown in Table 1.
[0119] The cherry stearate beads manufactured by NOF Corporation used above had the following component composition (4 mass % myristic acid, 30 mass % palmitic acid, 65 mass % stearic acid, and 1 mass % others).
[0120] (Example 10: Preparation of surface-treated calcium carbonate filler (E10)) In the same manner as in Example 1, the obtained synthetic calcium carbonate slurry was subjected to Ostwald aging to obtain a calcium carbonate having a BET specific surface area of 20.0 m 2 After the particles were grown to 10.0 g / g, the resulting calcium carbonate was used as a seed to add 10% by mass of calcium hydroxide to the calcium carbonate solid, and a seed compound was formed by reacting it with the CO gas discharged from the calcination furnace. The BET specific surface area was 17.0 m. 2 / g of calcium carbonate slurry was obtained.
[0121] A surface-treated calcium carbonate filler (E10) was obtained in the same manner as in Example 1 except that an aqueous solution of a phosphorus compound was prepared by adding 3.0 mass% of ultrasodium phosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass%, and a fatty acid salt obtained by saponifying 2.7 mass% of a saturated fatty acid (NAA-122 (lauric acid: 99%) manufactured by NOF Corporation) based on the calcium carbonate solid content with caustic soda to warm water to give a concentration of 10 mass% was added thereto. The physical property values of the obtained surface-treated calcium carbonate filler (E10) are shown in Table 1.
[0122] (Example 11: Preparation of surface-treated calcium carbonate filler (E11)) In the same manner as in Example 1, the obtained synthetic calcium carbonate slurry was subjected to Ostwald aging to obtain a calcium carbonate having a BET specific surface area of 24.0 m 2 After the particles were grown to a specific surface area of 20.0 m / g, 10% by mass of calcium hydroxide was added to the calcium carbonate solids as a seed, and the seed compound was reacted with the CO gas discharged from the calcination furnace to produce a calcium carbonate powder with a specific surface area of 20.0 m. 2 / g of calcium carbonate slurry was obtained.
[0123] A surface-treated calcium carbonate filler (E11) was obtained in the same manner as in Example 11 except that an aqueous solution of a phosphorus compound was prepared by adding 4.0 mass% of sodium ultraphosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass%, and a fatty acid salt obtained by saponifying a saturated fatty acid (NAA-122 (lauric acid: 99%) manufactured by NOF Corporation) with caustic soda to the calcium carbonate solid content to warm water to give a concentration of 10 mass% was added thereto. The physical property values of the obtained surface-treated calcium carbonate filler (E11) are shown in Table 1.
[0124] [Table 1]
[0125] (Comparative Example 1: Preparation of Surface-Treated Calcium Carbonate Filler (C1)) BET specific surface area 1.9m 2 While stirring heavy calcium carbonate (Super S manufactured by Maruo Calcium Co., Ltd.) of 100 g / g with a Super Mixer SMV(G)-100 manufactured by Kawata Co., Ltd., ultra sodium phosphate (Ultraporin manufactured by Taihei Chemical Industry Co., Ltd.) of 0.3 mass% based on the calcium carbonate solid content, which was prepared to have a concentration of 10 mass% in hot water, was added, and further saturated fatty acid (Stearic acid Sakura beads manufactured by NOF Corporation (saturated fatty acid rate 100%)) of 1.0 mass% based on the calcium carbonate solid content was added as a surface treatment agent, followed by stirring at 110°C for 0.5 hours to obtain a surface-treated calcium carbonate filler (C1). The physical property values of the obtained surface-treated calcium carbonate filler (C1) are shown in Table 2.
[0126] (Comparative Example 2: Preparation of Surface-Treated Calcium Carbonate Filler (C2)) The synthetic calcium carbonate slurry obtained in the same manner as in Example 1 was subjected to Ostwald aging to obtain a calcium carbonate slurry having a BET specific surface area of 30.0 m 2After the particles were grown to a specific surface area of 25.0 m / g, 10% by mass of calcium hydroxide was added to the calcium carbonate solids using the resulting calcium carbonate as a seed, and a seed compound was formed by reacting the calcium carbonate with the CO gas discharged from the calcination furnace. 2 / g of calcium carbonate slurry was obtained.
[0127] A surface-treated calcium carbonate filler (C2) was obtained in the same manner as in Example 1 except that an aqueous solution of a phosphorus compound was prepared by adding 1.2 mass% of ultrasodium phosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass%, and a saturated fatty acid soap (NONSAAL SN-1 (saturated fatty acid rate 100%) manufactured by NOF Corporation) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass% was added thereto. The physical property values of the obtained surface-treated calcium carbonate filler (C2) are shown in Table 2.
[0128] (Comparative Example 3: Preparation of Surface-Treated Calcium Carbonate Filler (C3)) A surface-treated calcium carbonate filler (C3) was obtained in the same manner as in Example 3 except that no phosphorus-based compound was added. The physical property values of the obtained surface-treated calcium carbonate filler (C3) are shown in Table 2.
[0129] (Comparative Example 4: Preparation of Surface-Treated Calcium Carbonate Filler (C4)) A surface-treated calcium carbonate filler (C4) was obtained in the same manner as in Example 3, except that an aqueous solution of a phosphorus-based compound prepared by adding 5.0 mass% sodium ultraphosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass% was used instead of the aqueous solution prepared in Example 3. The physical property values of the obtained surface-treated calcium carbonate filler (C4) are shown in Table 2.
[0130] (Comparative Example 5: Preparation of Surface-Treated Calcium Carbonate Filler (C5)) The synthetic calcium carbonate slurry obtained in the same manner as in Example 1 was subjected to Ostwald aging to obtain a calcium carbonate slurry having a BET specific surface area of 19.5 m 2 / g to obtain a calcium carbonate slurry.
[0131] A surface-treated calcium carbonate filler for resin (C5) was obtained in the same manner as in Example 1, except that an aqueous solution of a phosphorus compound was prepared by adding 1.0 mass% of ultrasodium phosphate (UltraPoline manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass%, and a saturated fatty acid soap (NonSal SN-1 manufactured by NOF Corporation) based on the calcium carbonate solid content to warm water to give a concentration of 10 mass% was added to the calcium carbonate slurry. The physical property values of the obtained surface-treated calcium carbonate filler (C5) are shown in Table 2. The physical properties of the obtained surface-treated calcium carbonate (C4) are shown in Table 2.
[0132] (Comparative Example 6: Preparation of Surface-Treated Calcium Carbonate Filler (C6)) The synthetic calcium carbonate slurry obtained in the same manner as in Example 1 was subjected to Ostwald aging to obtain a calcium carbonate slurry with a BET specific surface area of 16.0 m 2 / g, thereby obtaining a calcium carbonate slurry having a concentration of 10.0 mass %.
[0133] A surface-treated calcium carbonate filler (C6) was obtained in the same manner as in Example 1 except that an aqueous solution of a phosphorus compound was prepared by adding 1.67 mass% sodium hexametaphosphate (sodium hexametaphosphate manufactured by Taihei Chemical Industry Co., Ltd.) based on the calcium carbonate solid content to a concentration of 10 mass% in warm water, and a saturated fatty acid soap (NONSAAL SN-1 manufactured by NOF Corporation) based on the calcium carbonate solid content to a concentration of 10 mass% in warm water was added to the calcium carbonate slurry, and the mixture was stirred at 80° C. for 0.5 hours. The physical property values of the obtained surface-treated calcium carbonate filler (C6) are shown in Table 2.
[0134] [Table 2]
[0135] (Examples 12 to 22 and Comparative Examples 7 to 12: Preparation of pellets (PE1) to (PE11) and (PC1) to (PC6)) 30 parts by mass of the surface-treated calcium carbonate (E1) to (E11) and (C1) to (C6) produced in Examples 1 to 11 and Comparative Examples 1 to 6, 70 parts by mass of a polypropylene resin (Novatec PP FB3B manufactured by Japan Polypropylene Corporation: MFR 7.5 g / 10 min), and 1.0 part by weight of a phenol-based antioxidant (Irganox 1010 manufactured by BASF Japan Ltd.) were mixed to obtain a resin mixture of 10 kg. The mixture was melt-kneaded in a twin-screw kneader TEX25αIII manufactured by Japan Steel Works, Ltd. (JSW) equipped with a strainer having an opening of 100 μm at a cylinder setting temperature of 170° C., a screw rotation speed of 250 rpm, and a feed rate of 8 kg / hour. The mixture was then cut with a cold pelletizer manufactured by Inoue Seisakusho Co., Ltd. to produce pellets (PE1) to (PE11) and (PC1) to (PC6). The results of application evaluation of the obtained pellets (PE1) to (PE11) and (PC1) to (PC6) are shown in Tables 3 and 4.
[0136] (Comparative Example 13: Preparation of pellets (PC7)) Pellets (PC7) were prepared in the same manner as in Comparative Example 9 except that 1.0 part by weight of a phosphorus-based antioxidant (Irgafos 168 manufactured by BASF Japan Ltd.) was further added when mixing the surface-treated calcium carbonate filler, the polypropylene resin, and the phenol-based antioxidant. The results of the application evaluation of the obtained pellets (PC7) are shown in Table 4.
[0137] [Table 3]
[0138] [Table 4]
[0139] As shown in Tables 3 and 4, the pellets (PE1) to (PE11) produced in Examples 12 to 22 all had superior thermal oxidation stability and significantly reduced MFR change rates compared to the pellets (PC1) to (PC7) of Comparative Examples 7 to 13. There were also significant differences between the two in dispersibility and maximum stress (strength).
[0140] This shows that the surface-treated calcium carbonate fillers (PE1) to (PE11) prepared in Examples 1 to 11 have the ability to improve all of the stability, heat resistance, dispersibility, and strength of the obtained resin composition, as compared with the surface-treated calcium carbonate fillers (C1) to (C6) of Comparative Examples 1 to 6.
[0141] In this manner, the surface-treated calcium carbonate filler of the present invention can reduce resin burning and generation of aggregates during melt-kneading of a resin composition using the filler, can suppress clogging of a strainer, and can provide excellent operation stability. Furthermore, it can provide a polyolefin resin composition in which, for example, strength deterioration is unlikely to occur. [Industrial Applicability]
[0142] The present invention is useful, for example, in the fields of resin molding, architecture and housing, paint, and a wide range of related technical fields.
Claims
1. A surface-treated calcium carbonate filler satisfying the following formulas (a), (b), and (c): (a)2.0≦Sw≦20.0(m 2 / g) (b) 300≦Pw≦5000 (ppm) (c) 0.01≦Tw≦0.30 (mass%) The Sw is the BET specific surface area (m 2 / g), The Pw is the content (ppm) of the phosphorus element in the surface-treated calcium carbonate filler measured by an inductively coupled plasma (ICP) emission spectroscopic analyzer, The Tw is a weight loss value (% by mass) of the surface-treated calcium carbonate filler at 140° C. to 220° C. measured with a differential thermobalance device.
2. The surface-treated calcium carbonate filler according to claim 1, further satisfying the following formula (d): (d) 0.80≦bw≦1.50 The bw is a hue change rate calculated by the following formula using yellowness values (b values) measured by a spectrophotometer before and after continuous heating at 140° C. for 48 hours for a paste in which the surface-treated calcium carbonate filler and dioctyl phthalate (DOP) are mixed in a mass ratio of 3 to 7: Hue change rate (bw) = (b value of paste after heating / b value of paste before heating) It is.
3. The surface-treated calcium carbonate filler according to claim 1, further satisfying the following formulas (e), (f), and (g): (e) 0.10≦D50≦2.00 (μm) (f) 0.9≦(D90-D10) / D50≦2.0 (g) Da≦5.0 (μm) The D50 is a 50% diameter (μm) accumulated from the small particle side in a volume particle size distribution of the surface-treated calcium carbonate filler measured with a laser diffraction particle size distribution measuring device, The D90 is a 90% diameter (μm) accumulated from the small particle side in the volume particle size distribution of the surface-treated calcium carbonate filler measured with the laser diffraction particle size distribution measurement device, The D10 is a 10% diameter (μm) accumulated from the small particle side in the volume particle size distribution of the surface-treated calcium carbonate filler measured with the laser diffraction particle size distribution measurement device, The Da is the maximum particle size (µm) in the volume particle size distribution of the surface-treated calcium carbonate filler measured with the laser diffraction particle size distribution measurement device.
4. The surface-treated calcium carbonate filler according to claim 1, which is used for constituting a polyolefin-based resin composition.
5. A resin composition comprising a resin and the surface-treated calcium carbonate filler according to any one of claims 1 to 3.
6. The resin composition according to claim 5 , wherein the resin is a polyolefin resin.
7. A molded article comprising the resin composition according to claim 5.
8. The molded article according to claim 7, which has the form of a film.
Citation Information
Patent Citations
Surface-treated calcium carbonate filler, and resin composition and molded article using same
JP7338929B1
Calcium carbonate filler for resins, and resin composition containing same
WO2018088008A1
Surface-treated inorganic filler and resin composition containing the same compounded therewith
JP2002363443A
Microporous film
JP2004196917A
Filler for porous film and porous film containing it
JP2006169421A